The Seepage-Creep Numerical Simulation Model of Coal Measures Sandstone Based on Particle Discrete Element. (15th June 2022) - Liu, Wang; Meng, Fanfei; Pu, Hai; Wang, Jian; Zhang, Guohui; Yi, Qingyu
Abstract : The stability of the surrounding rock in the goaf is one of the main factors to ensure the safety of the mining production. In this study, a coupled numerical simulation model of particle flow code, computational fluid dynamics, and parallel-bounded stress corrosion (PFC-CFD-PSC model) was proposed to conduct the seepage-creep coupling simulation through PFC 5.0 software. Based on the mechanical results, the crack propagation law of the coal measure sandstone under the mining-induced seepage-creep coupling load was analyzed, and the distribution of pressure gradient in the fluid grid was studied. The results show that seepage pressure has a significant effect on the damage of the rock mass; the greater the seepage pressure on the coal measure sandstone model, the more penetration cracks are generated and the greater the degree of macroscopic damage. When the residual strength is 70% of the peak strength, the damage degree of the coal measure sandstone increases with the increase of the seepage pressure; except for the four corners, the pressure gradient of the fluid at the top of the rock mass model is relatively large. The maximum value of the fluid grid pressure gradient increases with the increasing seepage pressure; it increases slowly under the seepage pressure of less than 1.5 MPa and increases sharply under the seepage pressure of greater than 1.5 MPa.